Nghiên cứu mối quan hệ giữa các thông số ra trong quy hoạch thực nghiệm máy đánh bóng hạt nông sản - Lê, Công Huỳnh (Bộ Giáo dục và Đào tạo, 2013)
In experimental research on machiery response parameters are usually random quantuties. Establishing statistic relationships between response parsmeters by means or methord or correlative analysis enables to solve generalized optimization problems more simply. This method can be availably applies for experimental research on mashines by experimentation.